Towards Affective TV with Facial Expression Recognition - Valentim, Pedro A.; Barreto, Fábio; Muchaluat-Saade, Débora C. (Proceedings of the Life Improvement in Quality by Ubiquitous Experiences Workshop (LIQUE); 2021: Proceedings of the 1st Life Improvement in Quality by Ubiquitous Experiences WorkshopDO - 10.5753/lique.2021.15716, 2021)
Facial recognition techniques, fantasized in fiction movie classics, have already become reality. Such technology opens up a wide range of possibilities for different kinds of systems. From the point of view of interactive applications, facial expression as input data may be more immediate and more trustworthy to the user’s sentiment than the click of a button. For interactive television, facial expression recognition could be used for bringing broadcasters and viewers closer, enabling TV content to be personalized by the user sentiment. In fact, not only facial expression recognition, but any interaction that enables affective computing. In this work, we call this concept Affective TV. In order to support it, this work proposes facial expression recognition for digital TV applications. Our proposal is implemented and evaluated in the Ginga-NCL middleware, a digital TV standard used in several Latin American countries.